Evaluating Data Management Plans: Are They Good and Are They Effective? - Green, Peter; Cairns, Amy; White, Hollie (2019)
Since 2014, Curtin University Library has provided support to researchers in using the University’s in-house Data Management Planning (DMP) tool. The tool guides researchers through a series of questions on how they plan to collect, store, secure, and share their research data. Creation of the plan is a prerequisite for staff to obtain ethics approval and file storage. Uptake of the DMP has been excellent over that four years, but are the plans good and are they effective? In 2018, Curtin University Library chose to collaborate with a Masters by Coursework student, Amy Cairns, to undertake a study to analyse the quality and effectiveness of Research Data Management Plans. The core research question was whether Curtin’s DMP tool help researchers manage the data they collect. The study involved analysing the extensive dataset of four years of DMPs, and conducting a survey and focus groups with research staff who had used the DMP tool. The past DMP data provided useful information on which Faculties produced the most DMPs, how many had been updated, storage options, and peak times for creating DMPs. The survey and focus groups provided valuable feedback on whether the existence of a DMP had improved researcher practices. These activities asked researchers to consider why they completed a DMP, what prompted any updates of the DMP, and if the questions in the DMP had changed practices in how they organised data, stored it, and made it available. These findings will inform how the Library educates users in use of the Tool and refine other aspects of the research data management service. The practitioner-researcher collaboration between the Library and the research student was mutually beneficial, and we will continue to explore opportunities for similar arrangements in other service areas.